Evaluación de la implementación de mejoras sostenibles en una vivienda de interés prioritario (VIP) ubicada en la ciudad de Barranquilla (2021)
The construction of housing units, although it is an indispensable tool for a society to develop, generates a large amount of waste and inappropriate use of natural resources. This problem generates a need for study, on the one hand, in the construction area, to guarantee good use of resources and on the other hand, in how the Colombian Government seeks to comply with the Sustainable Development Goals, proposed by the United Nations in its agenda. 2030, speaking precisely of objective 11, called "Sustainable Cities and Communities", which aims to ensure the well-being and integrity of each being in habitable spaces based on methodologies that continuously improve the relationship between the community and the natural environment; To cover the problem, the execution of sustainable single-family housing projects is proposed, guaranteeing the well-being and integrity of the environment as well as the inhabitants. In developed countries, there are standardized sustainable policies and systems that contribute to the fulfillment of this objective, such as LEED, EDGE, and BREEAM certifications, systems that in Colombia are beginning to be implemented in buildings of great magnitude, but not in housing construction. single-family. What is sought with this research is to propose improvement ideas for a design implemented in the construction of priority interest dwellings in the city of Barranquilla, based on the EDGE certification criteria, thus contributing to the sustainable development of cities and communities.